ナンキョク カンソク ヨウ コガタ ムジン コウクウキ Ant-Plane ノ カイハツ ソノ カノウセイ ト カダイ - 船木, 實; フナキ, ミノル; Ant-Plane Group; Funaki, Minoru (2006)
P(論文) 南極の夏期間,沿岸地域で科学観測や氷状偵察に用いる小型無人飛行機の開発をAnt-Plane計画のもとで行っている.今までにGPSと気圧高度計,それにピトー管速度をもとに自動操縦する機体を4種開発した.Ant-Plane 2号機により桜島と鳥海山で飛行実験を試みた結果,風が弱い時は機体の位置精度は30 m以内で,極めて良い自動飛行が確認された.最大風速が22 m/sでも機体はウェイポイントに向けて飛行し,おおむね良好な直線飛行であったが,旋回時に風下側で大きくルートを逸脱した.風が弱い時は,三成分磁気抵抗型磁力計(総重量400 g)で10 nTの精度で空中磁場観測が可能であったが,強風時に風上に飛行する時は大きなノイズが発生し意味あるデータは得られなかった.Ant-Plane 4号機は500 kmの連続飛行と最高飛行高度5700 mを達成した.南極の夏期間沿岸地域で500 kmまでの航空機観測が小型無人飛行機で可能になったが,南極観測隊員が容易にAnt-Planeを使用するためには,簡易な離着陸やエンジン調整等の手法の確立が重要である. Four kinds of small drones (autonomous unmanned aerial vehicles UAV, so called Ant-Plane) are developed under the Ant-Plane project for scientific research and logistics in the coast region of Antarctica in austral summer. The Ant-Plane 2 cruised within 30 m of the planned course during calm weather at Sakurajima Volcano on Kyushu. During strong wind, 22 m/s, at Chokai Volcano, northern Honshu, the drone remained on course during straight flight but deviated when turning leeward. An onboard magneto-resistant magnetometer (400 g) recorded the variation of magnetic field with accuracy of 10 nT in calm wind, but strong magnetic noise was observed in strong wind, especially a head wind. The Ant-Plane 4 achieved a continuous flight of 500 km and the highest flight altitude of 5700 m. The Ant-Plane UAV can be used for various kinds of Antarctic, requires further development of techniques for easy takeoff and landing and easy start of engines. departmental bulletin paper